Epidemiology of ixodid ticks in buffaloes (Bubalus bubalis) of Punjab, India - Singh, N.K.; Rath, S.S. (Buffalo Bulletin, 2018)
A total of 3590 buffaloes of all age groups and sex were examined from various districts of Punjab state, India. The association between age, sex of host, season and the prevalence of ixodid ticks on animal level were investigated by multivariate logistic regression. The overall prevalence of ixodid ticks, Rhipicephalus (Boophilus) microplus, Hyalomma anatolicum anatolicum and mixed infestations were 57.68, 31.83, 19.08 and 6.76%, respectively. The results of multivariate analysis showed that the prevalence was associated with season (P<0.001; OR: 3.153; CI 95%: 2.69-3.69), host age (P<0.001; OR: 2.13; CI 95%: 1.67-2.73) and sex (P<0.001; OR: 0.416; CI 95%: 0.24-0.71). The prevalence of ixodid ticks were highest in monsoon season (74.48%) whereas, maximum prevalence of R. (B.) microplus and H. a. anatolicum were recorded in monsoon (44.73%) and summer (23.32%), respectively and the seasonal variation was significant (P<0.001). Further, higher tick infestation was recorded in calves ​